Research on Necessity and Development Strategy of Developing High-speed Maglev in China - Houwen ZHOU; Xu CHEN (机车电传动)
On the basis of reviewing the "dispute between high-speed maglev and high-speed railway" in the 1990s, the facing new situations and changes in the development of high-speed maglev in China were analyzed. Drawing on the relevant experience of the planning and construction of the Japan's central Shinkansen, the necessities of China's development of high-speed maglev were analyzed from following aspects: implementing the development strategy of transportation power, maintaining China's leading position in the transportation field, enriching the comprehensive transportation system, meeting passenger travel needs, driving the development of related industries, promoting the upgrading of industrial structure, and promoting the regional integration development, et. Finally,taking into account the national development strategy, economic development level, passenger travel needs, existing and planning transportation system, and other factors, the initial, short-term and long-term development strategies were proposed.